Question and Respond Types in Courtroom: A Forensic Linguistics Analysis - Lubis, Y. Basri Saktyus; Sinar, T. Silvana; Lubis, Masdiana (LingPoet: Journal of Linguistics and Literary Research, 2023)
Employing forensic Linguistics, this qualitative study describes types of question and respond in Providence, Rhode Island court proceedings. Four transcript case from the Traffict court of Providence, Rhode Island, United State of America were used as corpora in this study. Using Griffith Question Map ( Griffiths, 2006) and Cooperative Principle to approach the sudy. It was found that the are seven types of question raised by judge Frank Caprio ( Appropriate Closed Yes/No Question, Probing Question, Inappropriate Closed Yes/No question, Open question, opinoin or statement, leading question, and Multiple question) and three types of respond of defendant ( Maxim of Manner, Quality, and Relevance).